Fast Food Consumption Habits and Nutritional Status: A Descriptive Study Among Grade X Students at Senior High School 22 Surabaya - Ni Putu Ayu Diah Warapsari; Ani Intiyati; Nuning Marina Pengge; Ergia Latifolia (Journal of Nutrition Explorations, 2025)
Excessive fast food consumption and imbalanced eating habits in adolescents can negatively impact nutritional status and increase the risk of overweight and obesity. This study aimed to describe fast food consumption patterns and their relationship with nutritional status among 79 tenth-grade students at SMA Negeri 22 Surabaya, using a descriptive cross-sectional design and simple random sampling. Nutritional status was assessed using BMI-for-age (WHO 2007), and fast food consumption was measured using a validated Food Frequency Questionnaire (FFQ) through interviews. Data were analyzed using SPSS. Most respondents were male (63.3%) and aged 16 years (64.6%). A total of 58.2% had normal nutritional status, while 24.1% were overweight, 11.4% obese, and 6.3% underweight. Regarding fast food habits, 50.6% seldom consumed it, and 49.4% consumed it often. Cross-tabulation showed higher rates of overweight (14.1%) and obesity (10%) among those who often consumed fast food. These findings suggest a potential link between frequent fast food intake and overnutrition. Schools are encouraged to implement regular nutrition education to promote healthier eating habits among students.